Adição de oat fiber em produto cárneo reestruturado empanado de frango - Fiorentin, Cristiane (2014)
In recent years there has been a change in the life style of the population because of the facilities found to purchase food in the market, which has led to lower consumption of natural foods and consequently decreasing the consumption of foods with a source of dietary fiber. The project goal was to developed a restructured meat product breaded chicken add oat fiber, assessing the technological characteristics of insoluble fiber, develop formulations with different concentrations of oat fiber, determine the proximate composition, color, shear force, optical microscopy and sensory analysis of different formulations. The characterization of oat fiber showed that the particle size distribution corresponded between 38 and 75µm . The water holding capacity (WHC) of oat fiber resulted in 3.16 g of water per gram of sample and oil retention capacity (ORC) corresponded to 2.90 g oil per gram of sample. The result of the proximate composition of oat fiber was 9.88 % moisture, 3.39 % of ash, 0.60 % fat, 3.06 % protein and 83.12 % dietary fiber. For Proximal composition of breaded chicken made with different concentrations of oat fiber (3% , 4.5% and 6%) it was observed that increasing the addition of fiber resulted in a decrease in the protein and moisture , and was the inverse to the levels of lipids and mineral matter, significant difference (p<0.05) in the analysis of moisture, ash and protein . The content of dietary fiber in chicken fingers accompanied the percentage of added oat fiber in the formulation of 3 % and 4.5 %, but the formulation of 6 % did not match the percentage added, but remained with the highest fiber intake. All formulations could receive in labeling the attribute source of fiber, according to Brazilian law. In the analysis of color was no significant difference (p<0.05) between the samples analyzed for parameters L * and b *, however there was no significant difference (p>0.05) for the parameter a *. In the analysis of shear force no significant difference between samples (p>0.05). In optical microscopy, can verify that there was tendency of fat to bind with fiber Sensory analysis showed that the three formulations are equal, and there was no significant difference (p>0.05) for the attributes of color, taste and texture, however, juiciness attribute significant difference (p<0 05) between the samples. All formulations showed rates of buying interest. This work has proved possible to develop product formulations restructured with good behavior before the addition of insoluble fiber, with good acceptability to consumers and offering a product with an alternative source of fiber.